Collagenous and Lymphocytic Colitis: A Clinical and Histopathological Review - Johan Bohr; Martin Olesen; Curt Tysk; Gunnar Järnerot (Canadian Journal of Gastroenterology)
Collagenous colitis and lymphocytic colitis are newly described colitides that are only diagnosable microscopically; therefore, both are known under the umbrella term ’microscopic colitis’. This is a short review of the clinical findings, and epidemiological and basic observations of these relatively little described colitides belonging to the group of inflammatory bowel diseases.